2009
DOI: 10.1073/pnas.0909088106
|View full text |Cite
|
Sign up to set email alerts
|

Rapid equilibrium sampling initiated from nonequilibrium data

Abstract: Simulating the conformational dynamics of biomolecules is extremely difficult due to the rugged nature of their free energy landscapes and multiple long-lived, or metastable, states. Generalized ensemble (GE) algorithms, which have become popular in recent years, attempt to facilitate crossing between states at low temperatures by inducing a random walk in temperature space. Enthalpic barriers may be crossed more easily at high temperatures; however, entropic barriers will become more significant. This poses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
184
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 157 publications
(190 citation statements)
references
References 51 publications
6
184
0
Order By: Relevance
“…Previous work has demonstrated that this network theory is capable of quantitative agreement with experiments (6,(11)(12)(13) and we have now shown that it can also scale down to simple, generic models. Using this theory at both the quantitative and qualitative levels, we have provided an intuition for conformational changes as drastic as protein folding and this intuition has led to experimentally testable insights into the nature of protein free energy landscapes.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Previous work has demonstrated that this network theory is capable of quantitative agreement with experiments (6,(11)(12)(13) and we have now shown that it can also scale down to simple, generic models. Using this theory at both the quantitative and qualitative levels, we have provided an intuition for conformational changes as drastic as protein folding and this intuition has led to experimentally testable insights into the nature of protein free energy landscapes.…”
Section: Discussionsupporting
confidence: 57%
“…A number of recent works have provided validation for these networks by showing that they can yield quantitative agreement with experimentally derived structures and folding rates (6,(11)(12)(13). In particular, the predicted native state from our villin model (based on calculated free energies) had an rmsd to the crystal structure of approximately 1.8 Å (6).…”
mentioning
confidence: 97%
“…Also, the detection of important transitions might be automated, e.g., by means of applying Markov State Model approaches (39).…”
mentioning
confidence: 99%
“…Approaches such as Milestoning [35,117] and a Markovian state model (MSM) based adaptive seeding method [118] are promising for achieving long-time sampling. For example, the former has been successfully applied to elucidate complex conformational dynamics such as allosteric transitions in hemoglobin [119] and the myosin stroke [35].…”
Section: Discussionmentioning
confidence: 99%